Therapeutic updates on the management of tinea corporis or cruris in the era of Trichophyton Indotineae: Separating evidence from hype-A narrative review - Ananta Khurana; Savitha Sharath; Kabir Sardana; Anuradha Chowdhary; Sanjeet Panesar (Wolters Kluwer Medknow Publications, 2023)
The emergence and spread of Trichophyton indotineae (T. indotineae) has led to a sea change in the prescription practices of clinicians regarding the management of dermatophytic skin infections. An infection easily managed with a few weeks of antifungals, tinea corporis or cruris, is now often chronic and recurrent and requires prolonged treatment. Rising resistance to terbinafine, with documented squalene epoxidase (SQLE) gene mutations, and slow clinical response to itraconazole leave clinicians with limited treatment choices. However, in these testing times, it is essential that the tenets of antifungal stewardship be followed in making therapeutic decisions, and that the existing armamentarium of antifungals be used in rationale ways to counter this extremely common cutaneous infection, while keeping the growing drug resistance among dermatophytes in check. This review provides updated evidence on the use of various systemic antifungals for dermatophytic infection of the glabrous skin, especially with respect to the emerging T. indotineae species, which is gradually becoming a worldwide concern.